2022 American College of Rheumatology/European Alliance of Associations for Rheumatology classification criteria sets for three types of antineutrophilic cytoplasmic antibody-associated vasculitis - Yazici, Hasan; Tascilar, Koray; Yazici, Yusuf (Current Opinion in Rheumatology, 2023)
Purpose of reviewA critique of the recently published classification criteria for three main types of antineutrophilic cytoplasmic antibody (ANCA)-associated vasculitis.Recent findingsAn ACR and EULAR joint task force recently published classification criteria for three main types of ANCA-associated vasculitis. The criteria were based on patient histories and findings in nearly 7000 patients from 136 sites in 32 countries. As such the study represented hitherto the most intensive attempt to prepare classification criteria vasculitis. We propose, this truly intensive effort was, unfortunately, unsuccessful. There were two main mishaps. The first one was that the proposed criteria were not validated in an independent cohort. This is curious in that the sponsors, ACR and EULAR, require such independent cohorts for validation. The second mishap is that the concept that disease classification criteria need to be 100% sensitive and specific for a diagnosis is unrealistic. Moreover, all-purpose disease classification criteria are not respectful to scientific research and to the probabilistic nature of the art and the science of medicine.SummaryThe new ACR/EULAR ANCA-associated vasculitis guidelines have not been validated in independent cohorts. We propose replacing the term disease criteria with disease guidelines.
CRIS-Team Scopus Importer:2023-01-06
Keywords: ANCA-associated vasculitis; classification; criteria; guidelines; validation